KOTA TUA BARUS SEBAGAI DAERAH TUJUAN WISATA SEJARAH DI KABUPATEN TAPANULI TENGAH - Samuel Saut Marihot Silitonga; I Putu Anom (JURNAL DESTINASI PARIWISATA, 2016)
Barus Old City became one tourist destination for researchers of Islamic archeology, both domestically and abroad, especially in the Lobu Tua. All the existing tourism potential and supported by strategic location for a sightseeing trip make Old Town Barus very suitable to serve as a regional destination (DTW). But the existence of a tourist attraction that is not yet fully got the attention of government and society. It can be seen from the tourist attraction in Barus and a lack of information regarding the existing tourist attraction. Therefore, to make the Old City Barus as a historical tourist destination need for improvement of the tourism institute itself and also the community as a tourism people. Data collected by in-depth interviews and observation. In-depth interviews conducted by referring to the interview guide are explored and defined through preliminary observation / assessment. Some might ask them is what the potential of the old city of Barus addition to in-depth interviews, data collection is also done with the observation well at the sample location or at multiple locations in the surrounding historical attractions. Things were observed among the tourism potential in the history of the Old City of Barus Central Tapanuli. Results of this study showed that the potency owned Old Town Barus is historical attractions such as ancient tombs which are graves of Muslim missionaries of the past that Mahligai Tomb, Tomb of Boards of Appeal, the Tomb of Mr. Syech Machdun. All existing tourism potential and supported by strategic location for sightseeing trips make Old Town Barus very suitable to serve as a tourist destination. Efforts Preservation and Development of tourism potential in the Old City of Barus need any interference from the local community that would care little about the existence of these ancient tombs and also expect the local government to be more open eyes in the dig, as well as rectifying the historical record that the entry of Islam Indonesia through the Old City Barus, because in addition to as evidence of history that should be preserved its existence, the site of ancient tombs can also be used as a historical tourist destination in Central Tapanuli regency especially the old city Barus.